2023
DOI: 10.1177/10778012231159415
|View full text |Cite
|
Sign up to set email alerts
|

The Polish Variant of Patriarchy? Explaining the Relationship Between Gender Inequality and Violence Against Women in Poland

Abstract: The largest European victimization survey of violence against women (VAW), has revealed an interesting paradox: countries with the highest gender equality indices had the highest VAW indices, while countries with low gender equality, also had low VAW indices. The country with the lowest VAW rates was Poland. This article attempts to explain this paradox. First, the results of the FRA study regarding Poland and its methodological issues are described. As these explanations may prove insufficient, it is necessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Gender stereotypes are widespread in all societies and related to different forms of violence and women discrimination. Although literature has showed differences between countries with variants of patriarchy (Grzyb, 2023), and even some changes among generations, for instance in the Spanish society (Moya & Moya-Garófano, 2021), gender stereotypes still exist and influence our daily life leading to unequal access and distribution of resources such as education, employment, and healthcare (Willie & Kershaw, 2019). Gender differences and stereotypes, indeed, influence also the implication of women in different types of violent behaviour (Loinaz, 2016;Loinaz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender stereotypes are widespread in all societies and related to different forms of violence and women discrimination. Although literature has showed differences between countries with variants of patriarchy (Grzyb, 2023), and even some changes among generations, for instance in the Spanish society (Moya & Moya-Garófano, 2021), gender stereotypes still exist and influence our daily life leading to unequal access and distribution of resources such as education, employment, and healthcare (Willie & Kershaw, 2019). Gender differences and stereotypes, indeed, influence also the implication of women in different types of violent behaviour (Loinaz, 2016;Loinaz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems when investigating stereotypes and cognitive distortions is the measurement of the construct. Not only can there be differences in the way of manifesting or expressing themselves within the same culture (Grzyb, 2023;Ruiz-Hernández et al, 2020), but it is also known that the measure is not consistent or convergent with other objective indicators such as behaviors, as research on cognitive distortions has shown comparing parner violent men and the general population (Loinaz, 2014). On the other hand, issues such as the education or age of the participants in these studies do not have a clear direct reflection in the results, since these variables also depend on social, historical and generational changes that are difficult for studies to categorize (for example, knowing if the participant has been educated in a more egalitarian educational model or more macho classic values; to know if the family environment was also educated and has transmitted egalitarian values or perpetuated stereotypes, and so on).…”
Section: Discussionmentioning
confidence: 99%